2011
DOI: 10.1515/hf.2011.004
|View full text |Cite
|
Sign up to set email alerts
|

Fungi associated with bamboo and their decay capabilities

Abstract: Biological deterioration is the most important issue facing the use of bamboo as a bioresource. To identify the fungi responsible for bamboo degradation, isolates were obtained from three decaying bamboo species and evaluated. A total of 16 genera and 18 species of fungi were isolated and identified. The major fungi causing serious damage are Trametes versicolor and Arthrinium arundinis, which caused the largest weight losses in tests, of approximately 21.6% and 17.9%, respectively. This investigation confirms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 11 publications
4
19
0
2
Order By: Relevance
“…The species from the four Nigerian sites studied here showed variable mass loss, which classified the bamboo as a moderate to non-durable plant material. T. versicolor caused the highest mass loss (11.2 to 16.8%), similar to the results of Kim et al (2011) but higher values relative to the results of Suprapti (2010), who found mass losses in the range 4 to 7.2% with the same fungus. Significant differences (p<0.05) in mass loss were found when the bamboo samples were exposed to P. placenta (i.e., 5.4 to 13.4%), which was greater than the results of Suprapti (2010) (i.e., 2.4 to 4.5%).…”
Section: Durability and Treatability Of Bamboosupporting
confidence: 86%
“…The species from the four Nigerian sites studied here showed variable mass loss, which classified the bamboo as a moderate to non-durable plant material. T. versicolor caused the highest mass loss (11.2 to 16.8%), similar to the results of Kim et al (2011) but higher values relative to the results of Suprapti (2010), who found mass losses in the range 4 to 7.2% with the same fungus. Significant differences (p<0.05) in mass loss were found when the bamboo samples were exposed to P. placenta (i.e., 5.4 to 13.4%), which was greater than the results of Suprapti (2010) (i.e., 2.4 to 4.5%).…”
Section: Durability and Treatability Of Bamboosupporting
confidence: 86%
“…Thus, possible influences among the parameters, bamboo species, moisture content and nutrient addition, were rather indistinct for this fungus. Low decay was also measured on agar in preserving jars and in Kolle flasks (Schmidt et al 2011) which was already reported by Suprapti (2010) and Kim et al (2011). Abdurachim (1964) obtained 15% mass loss in Gigantochloa apus.…”
Section: = Hyphal Density C = Hyphal Coverage Of Samplesupporting
confidence: 79%
“…However, bamboo has a low natural durability and is attacked by fungi during storage, transport, processing and final use (Liese and Kumar 2003). There are several reports on its degradation by fungi (Liese 1959(Liese , 1985Abdurachim 1964, Mohanan 1997, Kim et al 2011, Suprapti 2010, Ma et al 2010, Schmidt et al 2011. The behaviour of bamboo against decay fungi is an important parameter in bamboo establishment and use.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, this interesting morphology has been found in different chemical systems under a variety of reaction conditions, e.g. for hydrothermally prepared ZnO [27], for CaCO 3 [28] obtained from carbonation and also for fluorapatite [29,30] grown from double diffusion crystallization. We here propose that the outer shell of initially formed densely packed spheres becomes porous in the course of hydrothermal treatment, accompanied by the decollation of seed crystals.…”
Section: Template-assisted Synthesis Of Bivomentioning
confidence: 88%